Profiling circular RNA in methamphetamine-treated primary cortical neurons identified novel circRNAs related to methamphetamine addiction. (14th May 2019) - Li, Junwei; Shi, Qingqing; Wang, Qian; Tan, Xu; Pang, Kunkun; Liu, Xiaoyu; Zhu, Shaowei; Xi, Kaiyan; Zhang, Jing; Gao, Qing; Hu, Yanlai; Sun, Jinhao
Highlights: We profiled circRNA expression in METH-treated primary cortical neurons via RNA sequencing. Profiling circRNA expression identifies novel circRNA. Homer1 and Tlk1 are highly associated with METH addiction. Abstract: Methamphetamine (METH) has been a worldwide health threat for years. Recent studies have reported that circular RNA (circRNA) are highly abundant and dynamically expressed in brain. However, connections between circRNA and METH-induced neurotoxicity remains indefinite. In the present study, primary cortical neurons were treated with METH in vitro. We profiled circRNA via high-throughput RNA sequencing and identified 2458 circRNAs. Bioinformatics analysis was performed to predict potential functions of these circRNAs which revealed several relevant pathways including 'morphine addiction' that may contribute to the pathogenesis of neuronal damage by METH. Especially, a METH-addicted mouse model was established with conditional place preference paradigm for validation of screened circRNAs. At last, we established co-expression networks of circRNAs with miRNAs and mRNAs to exhibit potential association among them. In conclusion, we firstly unveiled a role of circRNAs in METH-induced neuronal damage and METH addiction.